Proceedings of the Fourteenth Workshop on Innovative Use of NLP for Building Educational Applications 2019
DOI: 10.18653/v1/w19-4404
|View full text |Cite
|
Sign up to set email alerts
|

Computationally Modeling the Impact of Task-Appropriate Language Complexity and Accuracy on Human Grading of German Essays

Abstract: Computational linguistic research on the language complexity of student writing typically involves human ratings as a gold standard. However, educational science shows that teachers find it difficult to identify and cleanly separate accuracy, different aspects of complexity, contents, and structure. In this paper, we therefore explore the use of computational linguistic methods to investigate how taskappropriate complexity and accuracy relate to the grading of overall performance, content performance, and lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The development of writing accuracy has also been assessed in some corpus studies using automated or manual error annotation (Lavalley et al, 2015;Göpferich and Neumann, 2016). In Weiss et al (2019) we analyze the impact of linguistic complexity and accuracy on teacher grading behavior.…”
Section: Related Workmentioning
confidence: 99%
“…The development of writing accuracy has also been assessed in some corpus studies using automated or manual error annotation (Lavalley et al, 2015;Göpferich and Neumann, 2016). In Weiss et al (2019) we analyze the impact of linguistic complexity and accuracy on teacher grading behavior.…”
Section: Related Workmentioning
confidence: 99%
“…In principle, language ability should not be a factor in SAG grading reliability, because language correctness is not taken into account during grade assignment: Mistakes by non-native respondents should not adversely influence their grades. However, Weiss et al (2019) found a disproportionate impact of error rate (but not linguistic complexity) on final grades when investigating teacher grading of German written final exams. Therefore, language errors and lack or presence of linguistic complexity might conceivably have biased graders in our data sets, as well.…”
Section: Corpus Levelmentioning
confidence: 87%
“…Lexical diversity, or the variety of words used in a text, was assessed with the measure of textual, lexical diversity, calculated using the lexical_diversity package (version 0.1.1) and chosen due to its insensitivity to text length. 42 , 43 , 44 , 45 Lexical diversity reflects language proficiency; highly diverse text indicates the author is using a broad range of vocabulary to express their thoughts and ideas. 46 The textstat package (version 0.7.3) calculated the Flesch-Kincaid grade level, which is calculated from the average syllables per word and average words per sentence, and describes an English passage’s comprehensibility.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis was performed in Python with the pandas package (version 2.1.1) used to calculate word counts. Lexical diversity, or the variety of words used in a text, was assessed with the measure of textual, lexical diversity, calculated using the lexical_diversity package (version 0.1.1) and chosen due to its insensitivity to text length . Lexical diversity reflects language proficiency; highly diverse text indicates the author is using a broad range of vocabulary to express their thoughts and ideas .…”
Section: Methodsmentioning
confidence: 99%